Protective effects of GuanXinNing tablet (GXNT) on diabetic encephalopathy in zucker diabetic obesity (ZDF) rats - Yajing Li; Jiaojiao Chen; Haiye Tu; Quanxin Ma; Mulan Wang; Jie Chen; Minli Chen (BMC, 2023)
Abstract Background Diabetic encephalopathy (DE) is a complication of diabetes that leads to cognitive and behavioral decline. Utilizing safe and effective complementary and alternative medications for its management is a wise choice. Previous studies have shown that GuanXinNing Tablet (GXNT), an oral preparation primarily derived from two Chinese herbs, Salvia miltiorrhiza Bge. and Ligusticum chuanxiong Hort., exerts a beneficial neuroprotective effect. In this study, we explored the protective effects of GXNT on DE in male Zucker diabetic fatty (ZDF) rats induced by a high-fat diet, aiming to ascertain its significance and potential mechanisms. Methods ZDF rats were induced to develop type 2 diabetes (T2DM) with DE by a high-fat diet and treated with GXNT for 8 weeks until they were 20 weeks old. Throughout the experiment, the animals' vital parameters, such as body weight, were continuously monitored. Cognitive function was evaluated using the Y maze test. Biochemical kits were employed to analyze blood glucose, lipids, and vascular endothelial-related factors. Cerebrovascular lesions were assessed using magnetic resonance angiography (MRA) imaging. Brain lesions were evaluated using hematoxylin and eosin (H&E) staining and ultrastructure observation. IgG and albumin (ALB) leakage were detected using immunofluorescence. Results GXNT demonstrated an enhancement in the overall well-being of the animals. It notably improved cognitive and behavioral abilities, as demonstrated by extended retention time in the novel heterogeneous arm during the Y-maze test. GXNT effectively regulated glucose and lipid metabolism, reducing fasting and postprandial blood glucose, glycated hemoglobin (HbA1c), and total cholesterol (TC) levels. Additionally, it exhibited a protective effect on the vascular endothelium by reducing the serum TXB2/PGI2 ratio while elevating NO and PGI2 levels. Moreover, GXNT ameliorated stenosis and occlusion in cerebral vessel branches, increased the number of microvessels and neurons around the hippocampus, and improved microvascular occlusion in the cerebral cortex, along with addressing perivascular cell abnormalities. Immunofluorescence staining showed a decrease in the fluorescence intensity of IgG and ALB in the cerebral cortex. Conclusions GXNT demonstrated a highly satisfactory protective effect on DE in ZDF rats. Its mechanism of action could be based on the regulation of glucolipid metabolism and its protective effect on the vascular endothelium.